2009
DOI: 10.3844/ajassp.2009.1637.1646
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein-Mediated Efflux and Drug Sequestration in Lysosomes Confer Advantages of K562 Multidrug Resistance Sublines to Survive Prolonged Exposure to Cytotoxic Agents

Abstract: Problem statement: Cellular drug resistance to anticancer agents is major obstacle in cancer chemotherapy and the mechanisms by which these MDR cells possess for protecting themselves to survive prolonged exposure to cytotoxic agents still debating. The study aimed to clarify the role of P-glycoprotein (Pgp) and enhanced drug sequestration in lysosomes to confer the multidrug resistance K562 cells with varied degree of Pgp expression. Approach: Erythromyelogenous leukemic K562 and its corresponding Pgp-over ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Since we have previously demonstrated that the intracellular MDR transporters were also found localized on the intracellular organelle membrane and they also play important role on pumping the drugs from cytosol into these organelles for example in SiHa cells (Laochariyakul et al, 2003;Mankhetkorn and Garnier-Suillerot, 1998;Dechsupa and Mankhetkorn, 2009). In this study we preliminary determined that for K562/adr and GLC4/adr cells, the functional P-glycoprotein and MRP1 protein was localized on the plasma membrane (GarnierSuillerot et al, 2001).…”
Section: Discussionmentioning
confidence: 61%
“…Since we have previously demonstrated that the intracellular MDR transporters were also found localized on the intracellular organelle membrane and they also play important role on pumping the drugs from cytosol into these organelles for example in SiHa cells (Laochariyakul et al, 2003;Mankhetkorn and Garnier-Suillerot, 1998;Dechsupa and Mankhetkorn, 2009). In this study we preliminary determined that for K562/adr and GLC4/adr cells, the functional P-glycoprotein and MRP1 protein was localized on the plasma membrane (GarnierSuillerot et al, 2001).…”
Section: Discussionmentioning
confidence: 61%
“…Previously, we indicated that low energy/low-doses of medical diagnostic X-rays did not significantly change various biological end points such as hemolysis, osmotic fragility, fluorescence anisotropy, mitochondrial membrane potential, the cell cycle, and the number of apoptotic cells of irradiated cells as compared to corresponding non-irradiated groups at each time end point [8][9][10] . Figure 2 summarizes the results as histograms of the accumulation of acridine orange in lysosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Lysosomal function was studied by altering the accumulation of acridine orange (AO) in lysosomes. The staining method was modified from a previously published work 33,34 . Briefly, 10 6 cells were suspended in 2 mL PBS buffer, pH 7.25 at 37°C in the presence of 1µM AO for 5 minutes in the dark.…”
Section: Lysosomementioning
confidence: 99%